The Correlations Between Mentors‘ Leadership Competencies And The Functions Performed By The Mentors - Skarbaliene, Aelita (European Scientific Journal, ESJ, 2016)
Although it is acknowledged positive mentor’s influence to mentee’s development, but not many researches were done to find personal and professional qualities that makes mentor to perform his or her functions better. The lack of such researches encouraged to carry out the research and to determine if the mentor’s leadership competencies have an effect on performance of mentor’s functions, i.e. to determine the correlations between the mentor’s leadership competencies and the quality of mentor’s functions performed. It was determined average strong, statistically significant linear positive correlation between mentor’s leadership competences and the quality of mentor’s functions performed. This correlation means that if mentor has stronger leadership competences, he or she performs mentor‘s functions better.